Law Enforcement against the Criminal Action of Little Theft - Ahmad Faisol; Anis Mashdurohatun (Law Development Journal, 2021)
This study aims to identify and describe law enforcement against minor theft crimes based on Perma No. 2 of 2012. This study uses a normative juridical approach, which is descriptive and analytical in nature. The data used is secondary data obtained through library research, which is then analyzed qualitatively. The result of this research is that law enforcement against minor theft crimes based on Perma No.2 of 2012 is carried out by judges by imposing fines from the general minimum limit to the specific maximum that has been adjusted, depending on the judge's discretion to consider the ability of the defendant and the economic conditions of the local community. There is an adjustment in the amount of the fine, then the problem of the value of the criminal penalty which is felt to be too low will be resolved, and the punishable fines that are threatened will be more in accordance with the development of the community. Imposing a fine for the perpetrator of minor theft will be more beneficial, both for the perpetrator, the community and the state itself, while for the victim, they will also receive justice.